(untitled) (Global Journal of Management and Business Research, 2023)
The trade of agricultural products between China and Thailand is thriving especially China s import trade of agricultural products from Thailand Even in the period of significant external environmental disruptions to trade it has shown a vibrant and rapid growth China has already become Thailand s largest trading partner and export market for agricultural products This research is based on HS classification data from 2013 to 2022 studies the trade scale product structure and market share of China s import trade of agricultural products from Thailand It also analyzes the influencing factors from the perspectives of import demand export supply and opportunities for the further development It concludes that China s import of agricultural products from Thailand are growing rapidly the product structure has undergone significant changes and there is still great potential for further development in the future